The Effect of Empowerment and Emotional Intelligence on Innovation in Civil Servants - Suryo, Roy; Hamidah, Hamidah; Saptono, Ari (AIBPM Publisher, 2023)
This research aims to find out how the effect of empowerment and emotional intelligence is partially on innovation in civil servants. The civil servants used in this study were BPJS employees with a total sample of 110 respondents. The results of this study indicate that there is a positive and significant effect of empowerment on innovation. Emotional intelligence also has a positive and significant influence on innovation. The findings of this study indicate that emotional intelligence has the greatest influence compared to empowerment on employee innovation at BPJS. Suggestions for BPJS and further researchers are presented in this study.